Design and development process of a next-generation training system for spinal surgery. (December 2013) - Bausch, Gerold; Adermann, Jens; Andrack, Ben; Dengl, Markus; Handwerk, Jochen; Müller, Matthias; Seifert, Andreas; Steinke, Hanno; Sturm, Matthias; Korb, Werner; Meixensberger, Jürgen
For the development of a new-generation training system for spinal surgery, an iterative development cycle based on four steps was used. By using (i) empathy, (ii) cognitive model, (iii) prototyping and testing, and (iv) validation, an interdisciplinary development team was able to successfully build and validate a training system for lumbar disc surgery. The training system consists of a realistic training model based on synthetic materials and an accompanying training concept. It allows the training of different scenarios, starting from basic surgical tasks to complex surgeries with different complications. This article describes the development process and the results of the validation of the training system.